Lineage‐specific roles of the cytoplasmic polyadenylation factor CPEB4 in the regulation of oncogenic drivers in melanoma - Pérez‐Guijarro, E; Karras, P; Cifdaloz, M; Goding, C (Nature Publishing Group, 2016)
Nuclear 3’ end‐polyadenylation is essential for the transport, stability and translation of virtually all eukaryotic mRNAs. Poly(A) tail extension can also occur in the cytoplasm, but the transcripts involved are incompletely understood, particularly in cancer. Here we identify a lineage‐specific requirement of the cytoplasmic polyadenylation binding protein 4 (CPEB4) in malignant melanoma. Computational and histological analyses revealed a marked upregulation of CPEB4 at early stages of melanoma progression. Functionally, melanoma cells were found unexpectedly distinct from other tumor cell types in their strict dependency on CPEB4 not only to prevent mitotic aberrations, but to progress through G1/S cell cycle checkpoints. RNA immunoprecipitation, sequencing of bound transcripts and poly(A) length tests uncovered the melanoma drivers MITF and RAB27A within a cohesive network of melanoma‐enriched signaling hubs controlled by CPEB4, a feature validated in clinical biopsies. These results provide new mechanistic links between cytoplasmic polyadenylation and lineage specification in melanoma.